ผลของการสนับสนุนการจัดการตนเองต่อพฤติกรรมการดูแลเท้าของผู้สูงอายุที่เป็นโรคเบาหวานชนิดที่ 2 - ศรีสมทรง กรรณิการ์; จินตนาวัฒน์ ผศ.ดร.โรจนี; สุคำวัง ผศ.ดร. กนกพร (Journal of Thailand Nursing and Midwifery Council, 2017)
Objective: To study the effect of a self-management supporting program on foot care behavior among older persons with type 2 diabetes. Design: Quasi experimental research. Procedure: Purposive sampling was used to recruit participants from Thasala hospital and Noppitum hospital, Nakhon Si Thammarat province. Participants were assigned into the experimental and control groups; 22 persons in the experimental group and 26 persons in the control group. The experimental group attended the self-management supporting program for 6 weeks, while the control group did not participate in this self-management supporting program. The instruments used in this study consisted of self-management supporting program for foot care in the elderly, the self-management education manual, a videotape about foot care, videotape about foot exercise, and videotape about foot massage for older persons with type 2 diabetes, and the perceived self-efficacy questionnaire. Data collection tools consisted of the Demographic Data Recording Form and a Foot Care Behaviors Questionnaire. Data were analyzed using descriptive statistics, independent t-test, and paired t-test. Results: Older people with type 2 diabetes who attended the self-management supporting program had significantly higher foot care behaviors than that of the group who did not participate in the self-management supporting program at level of p < 0.001, and after attending the self-management supporting program, older people with type 2 diabetes had significantly higher foot care behaviors than before attending the program at level of p < 0.001. Recommendations: The results of this study indicate that the self-management support program can increase foot care behaviors among older people with type 2 diabetes who had category 1 at risk for developing foot ulcers. Keywords: self-management supporting program for foot care; foot care behaviors; Older Persons with Type 2 Diabetes Mellitus